Towards optimal management of the axilla in the context of a positive sentinel node biopsy in early breast cancer - Wazir, Umar (World J Clin Oncol, 2014)
The sentinel lymph node biopsy (SLNB) was initially pioneered for staging melanoma in 1994 and it has been subsequently validated by several trials, and has become the new standard of care for patients with clinically node negative invasive breast cancer. The focussed examination of fewer lymph nodes in addition to improvements in histopathological and molecular analysis has increased the rate at which micrometastases and isolated tumour cells are identified. In this article we review the literature regarding the optimal management of the axilla when the SLNB is positive for metastatic disease based on level 1 evidence derived from randomised clinical trials.